Why Did the Mayflower's Century-Long Course Gradually Shift Leftward? - LI, Daniel Ling (Journal of Research for Christianity in China (JRCC), 2025)
This paper first examines the three aspects of the “national character” imprinted on America by the Mayflower Compact: a conservative political consciousness rooted in Christian faith; values affirming individual striving, adventurous spirit, and the pursuit of wealth; and constitutional democracy born of fairness and the rule of law. It then explores the left-leaning crises that have occurred throughout American history. Finally, it analyzes the causes of America's political shift to the left, arguing that secularization accelerated the collapse of conservatism, which in turn further fueled the rise of radical leftist forces.